2018
DOI: 10.4018/ijvcsn.2018040101
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Potential Factors in Sticker Use Among Japanese Young Adults

Abstract: In text-based communication, people can now use not only emoticons and emoji, but also graphical symbols called stickers. This study focused on the use of stickers in text-based communication. A questionnaire asking subjects to individually rate the perceived usefulness of 25 features of stickers was prepared and used in a survey targeting 211 Japanese college students. The authors then explored potential factors in the roles of stickers. The study revealed three potential roles of stickers: “easy transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…This research has identified various motives for using stickers, including: (a) to support self-expression (e.g. Lee et al, 2016), especially as 'subtle nuances and nonverbal cues' (Kato et al, 2018); (b) to convey a specific meaning in place of text (e.g. Konrad et al, 2020); (c) to manage social status or to construct a desired image (e.g.…”
Section: Sticker Use In Computer-mediated Communicationmentioning
confidence: 99%
“…This research has identified various motives for using stickers, including: (a) to support self-expression (e.g. Lee et al, 2016), especially as 'subtle nuances and nonverbal cues' (Kato et al, 2018); (b) to convey a specific meaning in place of text (e.g. Konrad et al, 2020); (c) to manage social status or to construct a desired image (e.g.…”
Section: Sticker Use In Computer-mediated Communicationmentioning
confidence: 99%